E-COMMERCE IMPLEMENTATION MODEL IN INCREASING ROOM OCCUPANCY AT GRAND INNA KUTA HOTEL - Ni Gusti Ayu Nyoman Trisna Julyanti; I Putu Astawa; Nyoman Mastiani Nadra (Politeknik Negeri Bali, 2018)
This study examines the implementation of e-commerce at Grand Inna Kuta Hotel and its effect on room occupancy rate in the period of 2015 – 2017 . The study covered some topics including business to business (B2B) and businness to customer (B2C) as the independent variables, and room occupancy rate as dependent variable. The study used mixed methodology of both qualitative and quantitative approach. The primary data comes from the interview that conducted by the author of this paper with the hotel and marketing staffs. Cost of sale and occupancy rate of room would be the secondary data of this paper. Moreover, the methodology in collecting the data is using the observation method, interview, and documentation. Further, the data analysis techniques are using the descriptive statistical test to determine the effectiveness of the application of B2B and B2C to increase the occupancy rate of rooms in Grand Inna Kuta. The results show that B2B only contributed a small amount to the room occupancy rate of the Grand Inna Kuta. However, B2C made a good contribution to the hotel’s occupancy rate.